Effect of Artemisinin Based Combination Therapy on the Liver and Kidney of Patient Attending University Health Centre - Olugbenga , Matthew Ajulo; Obot , Onyong-Offiok Akpan; Oluwatoyin , Hephzibah Ajulo (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
African countries due to resistance to conventional antimalarial drugs adopted use of artemisinin-based combination therapy (ACTs). This study aimed at evaluating the effect of ACTs on liver and renal functions. Upon approval, patients attending the University Health Centre for treatment of uncomplicated malaria after receiving prescription for ACTs were recruited for the study following their consent. A 3ml blood was collected from the participants immediately after recruitment (Day 0) and seven days later. The participants started ACTs on the day of recruitment. The blood was analysed in the laboratory for alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and creatinine respectively. The data obtained at day 0 and 7 were compared by using descriptive analysis such as mean and standard deviation; t-test was used for statistical analysis and significance was considered at p ? 0.05. Seventy-four (74) patients participated including twenty-six (26) males and forty-eight (48) females with mean age of 37.56±13.96years and mean body mass index (BMI) of 25.92±2.99kg/m2. ALT was elevated in participants from 6.66±5.27IU/L to 6.71±5.48IU/L while creatinine clearance of male participants reduced from 139.10±69.11mL/min to134.25±23.87mL/min. The study showed that ACTs were associated with elevated ALT in participants and reduced renal function in males.